PEMANFAATAN PELEPAH DAUN SAWIT SEBAGAI PAKAN SUMBER SERAT: STRATEGI DAN RESPON PRODUKSI PADA SAPI POTONG - Puastuti, Wisri (Pastura, 2017)
Feed resources from the plantation is potential to develop cattle population in Indonesia. Utilization of oil palm frond as cattle feed is very limited due to several reasons. Oil palm frond is potential as feed in terms of both quantity and quality of nutrient. Availability of oil palm frond is around 5,872 kg DM/ha/year can meet the fiber requirement for 2 animal units. Part of oil palm frond which can be used as feed include leaf, frond and whole of oil palm frond chopped or shredded. Through processing can increase the crude protein content of oil palm frond from 10.3 to 19.5% and dry matter digestibility to 53.4%. Processing also extend the storing period, so it can be used as a feed stock. Giving up to 55% of the ration dry matter resulted average daily gain in beef cattle to 0.85 kg. It is concluded that oil palm frond can be used as a feed source of fiber through the proper way and support the optimal production of cattle. Key words: cattle, oil palm frond, source of fiber.